ESTIMATION OF ECOLOGICAL LOSSES AT ORGANIZATION OF AUTOMOBILE TRANSPORTATIONS - V. К. Jaroshevich; V. N. Sedjukevich; D. V. Kapsky (Наука и техника)
Ecological safety of automobile transport systems is considered on the basis of the account of transportation process efficiency. It is shown that ecological safety of transportations is estimated to a great extent by the automobile usage level in respect of run and capacity. It is proposed a criterion of a passenger transport system optimality on the basis of carrying capacity proceeding from ecological safety of transportation.